1983
DOI: 10.1073/pnas.80.6.1712
|View full text |Cite
|
Sign up to set email alerts
|

Allergen challenge of lung tissue from asthmatics elicits bronchial contraction that correlates with the release of leukotrienes C4, D4, and E4.

Abstract: The leukotrienes C4, D4, and E4, previously referred to as slow reacting substance of anaphylaxis, elicited longlasting contractions of bronchi isolated from two birch pollen-sensitive asthmatics. The leukotrienes were 1,000 times more potent on a molar basis than was histamine or prostaglandin F2a. Moreover, allergen released leukotrienes C4, D4, and E4 from the lung tissue of the asthmatics in amounts that appeared to correlate well to the anaphylactic bronchial contraction. Irrespectively of whether the lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
129
1
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 367 publications
(136 citation statements)
references
References 24 publications
5
129
1
1
Order By: Relevance
“…Similarly, contraction to antigen can be elicited in passively (Dunlop & Smith, 1975;Dunlop et al, 1977;Adams & Lichtenstein, 1979;Davis et al, 1982) and intrinsically sensitized human tracheobronchial smooth muscle (Davis et al, 1982;Dahlen et al, 1983). The nature of the mediators and mechanisms involved in ' Author for correspondence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, contraction to antigen can be elicited in passively (Dunlop & Smith, 1975;Dunlop et al, 1977;Adams & Lichtenstein, 1979;Davis et al, 1982) and intrinsically sensitized human tracheobronchial smooth muscle (Davis et al, 1982;Dahlen et al, 1983). The nature of the mediators and mechanisms involved in ' Author for correspondence.…”
Section: Introductionmentioning
confidence: 99%
“…this response have been the subject of extensive biochemical and pharmacological investigation over the years (Chand & Eyre, 1978;Adams & Lichtenstein, 1979;Hand & Buckner, 1979;Burka & Paterson, 1980;1981ab;Saad et al, 1983;De Nucci et al, 1986). Conclusions about the precise contribution of various mediators to the contractile response vary depending on the species studied (Dunlop & Smith, 1975;Dunlop et al, 1977;Dahlen et al, 1983;Jones et al, 1987), the type of antibody mediating the response (Andersson, 1980;Regal, 1984;Undem et al, 1985) the nature of the experiment (biochemical or functional response) and the experimental conditions such as the presence or absence of additional blocking drugs (Hand et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Human tracheal epithelial cells, chopped human bronchi, and human lung homogenates convert arachidonic acid mainly to 15-HETE (5,12). Lung specimens from asthmatic subjects produce more 15-HETE than specimens from nonasthmatic subjects (13)(14)(15). Increased amounts of 15-HETE have been found in bronchoalveolar lavage fluid (BALF) of antigenchallenged atopic asthmatic patients (16), in sputum samples from asthmatic subjects (17), and in nasal secretions from healthy control subjects (18).…”
mentioning
confidence: 99%
“…The CysLTs are released from human lung due to allergic subjects in response to challenge with allergen (Dahlen et al, 1983). Hanazawa et al (2000) showed significant increases in CysLTs in breath condensates of patients with moderate and severe asthma, compared with normal subjects.…”
Section: Discussionmentioning
confidence: 98%